2016
DOI: 10.1093/bja/aev297
|View full text |Cite
|
Sign up to set email alerts
|

The increasing recreational use of nitrous oxide: history revisited

Abstract: The usefulness of 'corrected' body mass index vs. self-reported body mass index: comparing the population distributions, sensitivity, specificity, and predictive utility of three correction equations using Canadian population-based data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 13 publications
1
67
0
Order By: Relevance
“…[42][43][44] There have been past reviews on inhalant and N 2 O abuse, including two recent overviews of recreational N 2 O use, prevalence and risk. 35,[45][46][47] Nonetheless, given the apparent increase in case reports on N 2 O abuse and reports of multiple sequelae previously of unknown etiology, an updated and comprehensive review of the case literature on N 2 O abuse and its clinical manifestations is indicated. In this review we summarize the neurologic, psychiatric, and other medical findings associated with N 2 O abuse.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44] There have been past reviews on inhalant and N 2 O abuse, including two recent overviews of recreational N 2 O use, prevalence and risk. 35,[45][46][47] Nonetheless, given the apparent increase in case reports on N 2 O abuse and reports of multiple sequelae previously of unknown etiology, an updated and comprehensive review of the case literature on N 2 O abuse and its clinical manifestations is indicated. In this review we summarize the neurologic, psychiatric, and other medical findings associated with N 2 O abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation of N 2 O, particularly in enclosed environments, can lead to hypoxia and asphyxiation 910. Although N 2 O inhalation is rarely fatal, at least three deaths have been attributed to N 2 O in the UK in each of the past five years, with eight cases in 2016 11…”
Section: Short and Long Term Harmsmentioning
confidence: 99%
“…N 2 O oxidises the cobalt ion in vitamin B 12 (cobalamin), impairing its function. The mechanism of subsequent neuronal injury is not known, but one theory is that cobalamin inactivation reduces the generation of methionine, which is necessary for the methylation of myelin sheath proteins 1012…”
Section: Short and Long Term Harmsmentioning
confidence: 99%
“…Another reason to trouble clinicians is the current widespread recreational and even addictive use of N20 among adolescents and young adults This could also worry parents whose children could benefit from it for procedural sedation. A misuse potential exists for many analgesic medications such as opioids, ketamine, and pregabalin, and conversely, products initially classified as drugs of abuse progressively obtain the medication status (cannabis).…”
mentioning
confidence: 99%